2006
DOI: 10.1037/0735-7044.120.6.1285
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional outcome following transient middle cerebral artery occlusion in the rat: Correlation between brain damage and behavioral impairment.

Abstract: The assessment of both histological and functional long-term outcomes after cerebral ischemia is increasingly recommended for preclinical studies. Whereas correlations between behavioral impairments and primary ischemic lesion are documented, little is known about their relationships with remote nonischemic regions that undergo secondary degeneration, such as the thalamus. Anesthetized rats were subjected to mild (30 min) or severe (60 min) occlusion of the middle cerebral artery. Two months after ischemia, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 65 publications
5
39
1
Order By: Relevance
“…Interestingly, measurements of the rat's performances in the neurological score were correlated with the volumes of lesion assessed on day 3 (r = 0.586, P < 0.001) and on day 16 (r = 0.574, P < 0.001). These results indicate that neurologic scoring is a reliable and sensitive measure, representative of the severity of ischemia (Freret et al, 2006a). In the limb placing test, results similar to the neurological score were observed.…”
Section: Behaviorsupporting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, measurements of the rat's performances in the neurological score were correlated with the volumes of lesion assessed on day 3 (r = 0.586, P < 0.001) and on day 16 (r = 0.574, P < 0.001). These results indicate that neurologic scoring is a reliable and sensitive measure, representative of the severity of ischemia (Freret et al, 2006a). In the limb placing test, results similar to the neurological score were observed.…”
Section: Behaviorsupporting
confidence: 65%
“…Thus, these two tests, previously validated in this model of ischemia by Freret et al (2006a), were performed for 3 weeks after cerebral ischemia.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Multiple studies have demonstrated secondary damage in the ipsilateral thalamus as the result of neuronal loss and retrograde and anterograde fiber degeneration [15][16][17][18][20][21][22][23][24] . These axonal tracts link the thalamus to other structures functioning as pathways for cerebral iron transport.…”
Section: Discussionmentioning
confidence: 99%
“…In other ROIs, no difference was found between patients and controls. No associa-In ischemic stroke, secondary changes in the ipsilateral thalamus outside the infarcted area have been demonstrated by several experimental and clinical studies [15][16][17][18][19][20][21][22][23][24] . A study in rats demonstrated hypointense areas in the thalamus after middle cerebral artery (MCA) occlusion on T2 * -w images which correlated with neuronal loss and iron deposition on histologic investigation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…neurological score (Bederson et al 1986), limb placing test (De Ryck et al 1989), chimney test, cylinder test (Bouet et al 2007)) -those tests would be mostly useful to assess acute phase after stroke, basically from 1 to 7 days) to more complex ones assessing both sensory and motor functions (i.e. adhesive removal , rotarod or staircase (Bouet et al 2007;Freret et al 2009;Freret et al 2006;Grabowski et al 1993;Modo et al 2000;Rogers et al 1997), which are conversely more relevant for long-term phase). Similarly, the memory tests have been developed to investigate cognitive functions (i.e.…”
Section: Long-term Functional Concernsmentioning
confidence: 99%